Fantasmas do rompimento da barragem: impactos na diversidade alfa e beta da ictiofauna na bacia do Rio Doce - Marina de Araújo Cruz (2024)
Continental aquatic environments are home to a great diversity of species, and environmental heterogeneity is one of the factors that influence it, promoting varied habitats and resources. However, human activities have homogenized these environments, reducing biodiversity. An example of this occurred in the Fundão dam collapse (2015), which dumped mining waste into the Rio Doce, causing environmental homogenization and biodiversity loss. This study investigated the ichthyofauna of the Rio Doce Basin, considering the possible remaining impacts of the collapse on fish diversity. The questions were: (1) Is alpha diversity affected by direct impact sites (sites where the mud passed through the river), indirect impact sites (tributaries connected to the mud passage sites), and isolated impact sites (above the others and separated by a hydroelectric dam)? (2) How are beta diversity and fish community composition affected by the different types of impact? My hypotheses are I) alpha diversity should be lower in direct impact sites, intermediate in indirect impact sites, and higher in isolated breach sites; II) the composition of fish species will be more similar (lower beta diversity) between direct impact sites when compared to indirect impact sites or isolated sites. Statistical analysis for alpha diversity included linear models for species richness, Shannon and Simpson diversity, and multivariate analyses for beta diversity (db-RDA, PERMANOVA, and PERMDISP). A total of 8,835 individuals from 77 species, 21 families, and 7 orders were collected. The results showed that alpha diversity of the ichthyofauna was not associated with treatments but with environmental variables. Richness was negatively influenced by the standard deviation of the thalweg depth. Shannon diversity was positively influenced by the standard deviation of the wetted width and negatively influenced by the standard deviation of the thalweg depth. Simpson diversity was positively influenced by the mean woody cover and negatively influenced by the geometric mean of the substrate diameter. Beta diversity, in turn, varied among treatments, being lower in areas of direct impact and higher in isolated areas. Redundancy analysis revealed that variation in fish community composition was mainly associated with the standard deviation of thalweg depth and wetted width in direct impact sites, and with flow heterogeneity in isolated and indirect impact sites. PERMANOVA indicated differences in species composition between direct and isolated impact sites. PERMDISP showed that, although there were no overall differences in community heterogeneity, isolated sites presented greater heterogeneity compared to direct impact sites. Alpha diversity was not influenced by treatments, probably due to the long history of environmental degradation in the basin that may have masked the effects of the dam failure but ended up highlighting the importance of environmental variables. On the other hand, beta diversity reflected lower heterogeneity in direct impact areas, possibly related to the remnant conditions of the dam failure. These results highlight the importance of environmental variables and suggest that the impacts of the dam failure still influence the structure of fish communities.